Enhancing Financial Literacy of Indonesian Migrant Workers in Malaysia through the Sikapi Uangmu Application - Ariyani Rahmawati; Fahri Ahzar; Samsul Rosadi (International Journal Of Community Service, 2024)
This community service program aims to improve the financial literacy of Indonesian Migrant Workers in Malaysia through direct training and digital technology, specifically, the Sikapi Uangmu application developed by the Financial Services Authority. Indonesian Migrant Workers often face challenges in managing their income, particularly in budgeting, investing, and handling debt. This program is designed to equip them with practical financial skills, enabling them to reduce financial risks and prepare for a more stable financial future. The results of this community service program indicate a significant improvement in Indonesian Migrant Workers' ability to manage their finances, including budgeting, selecting safe investments, and managing debt. The Sikapi Uangmu application provides easy and interactive access to financial information, allowing Indonesian Migrant Workers to engage in self-directed learning. Although the program has been successful, several challenges still need to be addressed, such as the digital divide and resistance to changing financial behaviors. Overall, the program has had both short-term and long-term positive impacts on Indonesian Migrant Workers in Malaysia and their families in Indonesia. However, its sustainability requires further adjustments to overcome technological barriers and to support more sustainable financial behavior changes